Cogito, ergo og sum - Fragmenter fra de efterladte skrifter (1885) - Nietzsche, Friedrich (Slagmark - Tidsskrift for idéhistorie, 2008)
Cogito, ergo og sum - Fragmenter fra de efterladte skrifter (1885)